1998
DOI: 10.1046/j.1523-1747.1998.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygosity for a Recessive Glycine Substitution and a Splice Site Mutation in the COL7A1 Gene Causes an Unusually Mild Form of Localized Recessive Dystrophic Epidermolysis Bullosa

Abstract: Type VII collagen is the major component of anchoring fibrils, adhesion structures of stratified epithelia that span the basement membrane region and papillary dermis. Mutations in the gene COL7A1 encoding type VII collagen cause dystrophic epidermolysis bullosa, a clinically heterogeneous autosomal dominant or recessive blistering disorder of the skin and mucous membranes. In this report, we investigate three siblings affected by an unusually mild form of localized recessive dystrophic epidermolysis bullosa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…However, the four glycine codons involved in RDEB-I with limited acral involvement have been reported in the RDEB-sev gen or DDEB phenotypes. In contrast, of the glycine codons involved in the RDEB-I ‘mucosal only’ phenotype, only glycine codon 1347 was reported in other, milder RDEB phenotypes 10 29 31…”
Section: Discussionmentioning
confidence: 98%
“…However, the four glycine codons involved in RDEB-I with limited acral involvement have been reported in the RDEB-sev gen or DDEB phenotypes. In contrast, of the glycine codons involved in the RDEB-I ‘mucosal only’ phenotype, only glycine codon 1347 was reported in other, milder RDEB phenotypes 10 29 31…”
Section: Discussionmentioning
confidence: 98%
“…Donor splice-site mutations of genes other than COL17A1 have been observed in epidermolysis bullosa patients. In a number of cases this resulted in a similar effect on transcription, namely activation of cryptic splice sites and exon skipping (Gardella et al, 1996;Posteraro et al, 1998;Terracina et al, 1998;Weil et al, 1988). In some patients, this was accompanied by a milder phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The hairless gene product is a transcriptional co-regulator with a single zinc-finger domain, which is highly expressed in the skin and the brain [7][8][9]. Furthermore, mutations in the hairless (HR) gene were identified in many APL families and to date, more than 30 hairless mutations have been reported [10][11][12][13][14][15][16][17][18]. Although APL could potentially be diagnosed by its clinical features alone, or by skin biopsy, APL remains frequently misdiagnosed as the more common disorder, alopecia universalis (AU).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many more mutations are likely to be discovered, since APL appears to be more common than previously considered [15]. To date, HR mutations have been found in APL patients from various ethnic backgrounds, including Pakistani, Mediterranean, Arab Palestinian, Caucasians, Japanese and Polish [10][11][12][13][14][15][16][17][18]. In this study, we identified three Pakistani families originating from different regions of Pakistan with clinical manifestations of APL and high degree of consanguinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation